On the ``Active spacer and stabilizer'' role of Zn in Cu1-xZnxFe2O4 in the selective mono-N-methylation of aniline: XPS and catalysis study - Vijayaraj, Munusamy; Gopinath, Chinnakonda S. (Journal of Catalysis, 2006)
A systematic catalytic methylation study on ferrospinel materials led to the selective production of N-methylaniline (NMA) with Cu1-xZnxFe2O4. Aniline methylation was carried out on Cu1-xZnxFe2O4 with a feed composition of CH3OH:PhNH2:H2O = 3:1:1 at 513-633 K. NMA was formed selectively on all of the catalyst compositions, with trace amounts of secondary products under most of the conditions. Cu0.5Zn0.5Fe2O4 composition showed high catalytic activity and stability up to 100 h. Although the Cu2+ was responsible for methylation activity, Zn2+ enhanced the overall stability of the catalyst system. XPS investigations revealed that the degree of Cu2+ reduction decreased dramatically from x = 0.05/0.25 to 0.5/0.75 on spent catalysts. TPR studies indicated that the reducibility of Cu2+ decreased from fully reducible at 523 K with Cu-rich compositions to partially reducible at 573 K on x = 0.5. Stable activity observed on Cu0.5Zn0.5Fe2O4 can be attributed to the highly heterogeneous distribution of metal ions. This heterogeneous distribution indicates an important role of zinc, likely as an ``active spacer cum stabilizee' that hinders the reduction of active Cu2+ and contributes to prolonged activity. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Aniline; Ferrite; N-methylaniline; N-methylation; spacer; stabilizer; surface distribution; TPR; XPS

Magnetic and Mossbauer spectroscopic studies of NiZn ferrite nanoparticles synthesized by a combustion method - Sreeja, V.; Vijayanand, S.; Deka, Sasanka; Joy, Pattayil Alias (Hyperfine Interactions, 2008)
The properties of nanocrystalline Ni(0.5)Zn(0.5)Fe(2)O(4) synthesized by an auto-combustion method have been investigated by magnetic measurements and Mossbauer spectroscopy. The as-synthesized single phase nanosized ferrite powder is annealed at different temperatures in the range 673-1,273 K to obtain nanoparticles of different sizes. The powders are characterized by powder X-ray diffraction, vibrating sample magnetometer, transmission electron microscopy and Mossbauer spectroscopy. The as-synthesized powder with average particle size of similar to 9 nm is superparamagnetic. Magnetic transition temperature increases up to 665 K for the nanosized powder as compared to the transition temperature of 548 K for the bulk ferrite. This has been confirmed as due to the abnormal cation distribution, as evidenced from room temperature Mossbauer spectroscopic studies.
Keywords: Ferrite; magnetic properties; Mossbauer spectroscopy; Nanoparticles

Physicomechanical and magnetic properties of neoprene based rubber ferrite composites - Prema, K. H.; Kurian, Philip; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Polymer-Plastics Technology and Engineering, 2008)
Fine (approximately 18nm) particles of nickel ferrite were synthesized by the sol-gel technique, and their structural properties were evaluated by X-ray diffraction. Neoprene-based rubber ferrite composites were prepared by incorporating these nickel ferrite powders in the rubber matrix according to a specific recipe. The cure characteristics were analyzed, and the samples were molded into particular shapes whose properties were determined according to ASTM standards. Magnetization studies were carried out using a Vibrating Sample Magnetometer. This study indicates that neoprene rubber-based flexible magnets with desired magnetic properties and appropriate mechanical properties can be prepared by incorporating an adequate amount of nanoscale nickel ferrite particles within the rubber matrix.
Keywords: Ferrite; ferrite composites; flexible magnets; neoprene rubber; rubber; Sol-gel method

Magnetic and dielectric properties of nanophase manganese-substituted lithium ferrite - Hankare, P. P.; Patil, R. P.; Sankpal, U. B.; Jadhav, S. D.; Mulla, Imtiaz S.; Jadhav, K. M.; Chougule, B. K. (Journal of Magnetism and Magnetic Materials, 2009)
Nanocrystalline manganese-substituted lithium ferrites viz. Li0.5Fe2.5-xMnxO4 (2.5 <= x >= 0) were prepared by sol-gel autocombustion method. X-ray diffraction analysis confirmed that as the concentration of manganese increases the cubic phase changes to the tetragonal phase. The variation of saturation magnetization was studied as a function of manganese content. All the compositions indicate that they are ferrimagnetic in nature. The dielectric constant, dielectric loss tangent and ac conductivity of all samples were measured at room temperature as a function of frequency. These parameters decrease with increase in frequency for all of the samples. The substitution of manganese plays an important role in changing the structural and magnetic properties of these ferrites. The compositional variation of dielectric constant and d.c. resistivity shows an inverse trend of variation with each other. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: dielectric constant; Ferrite; Magnetization; X-ray diffraction

Single step synthesis and properties of M/MFe2O4 and PVDF/M/MFe2O4 (M = Co, Ni) magnetic nanocomposites - Deka, Sasanka; Joy, Pattayil Alias; Kumar, A. Pratheep (Science of Advanced Materials, 2009)
Metal/ferrite nanocomposites (M/MFe2O4; M = Co, Ni), consisting of nanoparticles of a metal and the corresponding metal ferrite, have been synthesized under in situ conditions by a simple and single step process. The metal/ferrite nanocomposites embedded in a polymer matrix have been prepared by a simple hot-pressing method. The performance parameters such as magnetization, coercivity, permeability and dielectric constant of the two- and three-phase nanocomposite systems are compared. The coercivity increases and the permeability decreases with increasing polymer content in the three-phase composite. Enhancement of the dielectric constant is observed at low frequencies.
Keywords: Dielectric; Ferrite; magnetic properties; Nanocomposite; Nanocrystalline; permeability

Influence of palladium on gas-sensing performance of magnesium ferrite nanoparticles - Darshane, Sonali L.; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2010)
Commercial ferrites with high densities are mostly used in the electromagnetic devices, which require high temperature synthesis. In this article the gas-sensing characteristics of pure and Pd-doped MgFe(2)O(4) powder has been discussed. The synthesis has been carried out by using a simple molten salt method. This method facilitates rapid synthesis at comparatively lower temperature enabling formation of nanostructures, suitable for the gas-sensing application. Various physicochemical techniques have been used for the characterization of samples. X-ray diffraction analysis confirmed the single-phase formation of pure and Pd-doped MgFe(2)O(4) having crystallite size 15-20 nm. Pure MgFe(2)O(4) showed highest responses towards liquid petroleum gas (LPG) at 350 degrees C while, on doping with Pd the highest response shifted towards lower operating temperature of similar to 200 degrees C. Pure MgFe(2)O(4) exhibited some response towards 200 ppm of LPG which markedly increased on doping of palladium (Pd). The probable mechanism is proposed to explain the selective response towards LPG. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Doping; Ferrite; LPG sensor; Molten salt synthesis; Nanostructures

Liquefied petroleum gas sensing performance of cerium doped copper ferrite - Khandekar, M. S.; Tarwal, N. L.; Patil, J. Y.; Shaikh, F. I.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2013)
Undoped and cerium (Ce) doped nanocrystalline copper ferrite (CuFe2O4) materials were synthesized via the molten-salt (M-S) method. Effects of Ce doping on the structural, morphological and gas sensing properties of the CuFe2O4 ferrite have been investigated. X-ray diffraction (XRD) analysis revealed the formation of spinel CuFe2O4. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) investigations showed that the synthesized ferrite is made up of very fine spherical nanoparticles. Moreover, the gas sensing properties of sintered samples were studied towards different reducing gases such as liquefied petroleum gas (LPG), acetone, ethanol and ammonia. The sample with 4% cerium doped CuFe2O4 (Ce4) showed the maximum gas sensitivity (86%) towards LPG with fast response time of 5 s and good recovery time of 68 s. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ferrite; Gas sensor; Molten-salt method; TEM

Nanocrystalline Ce doped CoFe2O4 as an acetone gas sensor - Khandekar, M. S.; Tarwal, N. L.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2014)
Nanocrystalline CoFe2-xCexO4 ferrites (x=0, 0.04, 0.08) were synthesized by using the inexpensive, simple and eco-friendly molten-salt (M-S) method. Effects of Ce doping on the structural, morphological and gas sensing properties of the CoFe2O4 ferrite were investigated. X-ray diffraction (XRD) analysis revealed the formation of spinel CoFe2O4. Transmission electron microscopy (TEM) investigations showed that the synthesized ferrite is made up of very fine spherical nanoparticles. Furthermore, the gas response of nanocrystalline ferrite materials was investigated in the temperature range of 200-450 degrees C toward the reducing gases like liquefied petroleum gas (LPG), acetone, ethanol and ammonia. The sensor response was found to be sensitive and selective toward acetone as compared to other reducing gases. It is observed that the addition of Ce (4 wt%) strongly influenced the response and the operating temperature of the sensor material and thus can serve as acetone-sensing sensors. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: CoFe2O4; Ferrite; Gas sensor; Molten-salt method; TEM

High-performing PGM-free AEMFC cathodes from carbon-supported cobalt ferrite nanoparticles - Peng, Xiong; Kashyap, Varchaswal; Ng, Benjamin; Kurungot, Sreekumar; Wang, Lianqin; Varcoe, John R.; Mustain, William E. (Catalysts, 2019)
Efficient and durable non-precious metal electrocatalysts for the oxygen reduction reaction (ORR) are highly desirable for several electrochemical devices, including anion exchange membrane fuel cells (AEMFCs). Here, cobalt ferrite (CF) nanoparticles supported on Vulcan XC-72 carbon (CF-VC) were created through a facile, scalable solvothermal method. The nano-sized CF particles were spherical with a narrow particle size distribution. The CF-VC catalyst showed good ORR activity, possessing a half-wave potential of 0.71 V. Although the intrinsic activity of the CF-VC catalyst was not as high as some other platinum group metal (PGM)-free catalysts in the literature, where this catalyst really shined was in operating AEMFCs. When used as the cathode in a single cell 5 cm(-2) AEMFC, the CF-VC containing electrode was able to achieve a peak power density of 1350 mW cm(-2) (iR-corrected: 1660 mW cm(-2)) and a mass transport limited current density of more than 4 A cm(-2) operating on H-2/O-2. Operating on H-2/Air (CO2-free), the same cathode was able to achieve a peak power density of 670 mW cm(-2) (iR-corrected: 730 mW cm(-2)) and a mass transport limited current density of more than 2 A cm(-2). These peak power and achievable current densities are among the highest reported values in the literature to date.
Keywords: AEMFC; cobalt; Ferrite; high-performing; non-PGM; vulcan

Magnetic and magnetoelastic properties of Ni-substituted cobalt ferrite - Bhame, Shekhar D.; Shirolkar, Mandar M.; Joy, Pattayil A. (IEEE Magnetics Letters, 2021)
In this letter, magnetic and magnetostriction studies were performed on spinel ferrite Co1-xNixFe2O4 (CNF series) with 0.0 < x < 0.5. All the samples were synthesized by the conventional ceramic method and confirmed to be forming pure spinel phase. The unit cell parameter showed gradual decrease with increasing Ni content. A linear decrease in saturation magnetization (M-s) and coercivity (H-c) was observed with increasing Ni substitution, which could be attributed to reduced magneto-crystalline anisotropy. The room temperature magnetostriction studies revealed a slow decrease in maximum magnetostriction, and interestingly, for 20% reduction of cobalt concentration, i.e., for x = 0.2, a magnetostrictive strain of -164 ppm and substantially high stress sensitivity of -56 x 10(-6) A(-1) m were observed, making Co0.8Ni0.2Fe2O4 suitable for application as a magnetostrictive stress-sensing material.
Keywords: Ferrite; Magnetism in solids; Magnetostriction; oxide; stress sensing

Magnetostriction studies on transition metal substituted cobalt ferrite - Bhame, D. Shekhar; Bhapkar, Abhishek; Shirolkar, Mandar M.; Joy, Pattayil A. (Journal of the Indian Chemical Society, 2022)
Structural, magnetic and microstructural properties of transition metal (TM) substituted cobalt ferrite Co0.9TM0.1Fe2O4 (where TM = Ti, Cr, Mn, Ni and Cu and Zn) were investigated. The present study shows marked dependence of the magnetostriction on the concentration of the substituted transition metal ions for Cobalt in CoFe2O4. The magnetic characteristics of the prepared compositions such as coercivity, anisotropy constant and saturation magnetization changed significantly on transition metal substitution. The present study shows the way to tune the anisotropy of cobalt ferrite by effective substitution of other transition metal ions for Co which subsequently affects the stress sensing performance by changing the slope of the magnetostriction curve. Apart from the magnetic properties the microstructure can also be effectively modified by substitution of other transition metal ions. Only 10% substitution of cobalt showed drastic influence on magnetostriction and slope of magnetostriction curve. The composition with 10% nickel Co0.9Ni0.1Fe2O4 exhibited maximum slope for the magnetostriction curve of -53.7 ppm/Oe, along with reasonably high magnitude of strain of 186 ppm making it a suitable for exploring stress sensing applications.
Keywords: Ferrite; Magnetoelastic; Magnetostriction; oxide; stress sensing